Chromosome-level genome assembly and annotation of a sea toad (Chaunax sp.) - Zifeng Zhan; Yanshuo Liang; Jiehong Wei; Jing Liu; Kuidong Xu (Scientific Data)
Abstract The sea toad genus Chaunax is a group of small benthic fishes that predominantly inhabiting the deep seas of the Atlantic, Indian, and Pacific Oceans. Although they have the potential to make excellent systems for studies of evolutionary adaptation to deep-sea environments, genomic research on Chaunax has been hindered by a scarcity of high-quality genomic resources. We present a chromosome-scale genome assembly of a Chaunax specimen generated using PacBio long-read sequencing and high-throughput chromosome conformation capture technology. The size of the assembled genome was 706.94 Mb, with a contig N50 of 15.24 Mb and scaffold N50 of 29.42 Mb. Approximately 96.11% of assembled sequences were anchored and oriented onto 24 pseudo-chromosomes. The genome contained 213.47 Mb repetitive sequences, 25,280 protein-coding genes, and 5,090 non-coding RNAs. The high ratio of complete BUSCO genes (97.20%) indicates high quality of genome assembly. The chromosomal-level reference genome of Chaunax sp. provides a preliminary molecular basis for understanding deep-sea adaptation and phenotypic evolution as well as an important reference for whole-genome sequencing of related species.